The PerFect™ Lipid Optimizer Kit for Maximizing Lipid-Mediated Transfection of Eukaryotic Cells. (May 1997) - Griffiths, T.; Russell, M.; Froning, K.; Brown, B.D.; Scanlon, S.M.; Almazan, M.; Marcil, R.; Hoeffler, J.P.
The transfection efficiencies of a panel of eight uniquely different lipid reagents has been evaluated with two other commercially available lipids for use in transfecting a diversity of eukaryotic cell lines. The PerFect™ lipids are available individually or together in an optimization panel format that can be tested in any given cell line, enabling one to evaluate the optimal lipid for transfecting each individual cell line. Our results demonstrate that no single lipid is optimal for plasmid transfection over a broad range of cell types, thus emphasizing the need for multiple unique lipid reagents and a simple format for testing their transfection efficiency on a given cell type.